Involvement of VAT‐1 in Phosphatidylserine Transfer from the Endoplasmic Reticulum to Mitochondria. (25th October 2015) - Junker, Mirco; Rapoport, Tom A.
Abstract : How lipids are transported into mitochondria is only poorly understood. Here, we have reconstituted phosphatidylserine (PS) transport from the ER into mitochondria using Xenopus egg components. Our results indicate that cytosolic factors are required, whereas a stable physical contact between the organelles is not essential. We identified VAT‐1 as a cytosolic protein that interacts with a photoreactive PS analog. Our functional experiments suggest that VAT‐1 has a role in PS transport into mitochondria. Abstract : Mitochondria receive phosphatidylserine (PS) from the endoplasmic reticulum (ER), but how PS is moved from the ER to mitochondria is unclear. Current models postulate a physical link between the organelles, but no involvement of cytosolic proteins. Here, we have reconstituted PS transport from the ER to mitochondria in vitro using Xenopus egg components. Transport is independent of ER proteins, but is dependent on a cytosolic factor that has a preferential affinity for PS. Crosslinking with a photoactivatable PS analog identified VAT‐1 as a candidate for a cytosolic PS transport protein. Recombinant, purified VAT‐1 stimulated PS transport into mitochondria and depletion of VAT‐1 from Xenopus cytosol with specific antibodies led to a reduction of transport. Our results suggest that cytosolic factors have a role in PS transport from the ER to mitochondria, implicate VAT‐1 in the transport process, and indicate that physical contact between the organelles is not essential.